2008
DOI: 10.1071/ch07079
|View full text |Cite
|
Sign up to set email alerts
|

Cyanuric Chloride: an Efficient Catalyst for Ring Opening of Epoxides with Thiols Under Solvent-Free Conditions

Abstract: 2,4,6-Trichloro-1,3,5-triazine-catalyzed convenient and efficient ring opening of epoxides with thiols under solvent-free conditions is described. Short reaction time, mild reaction conditions, inexpensive and readily available catalyst, and excellent yields of products are attractive features of this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Bandgar and co-workers developed 2,4,6-trichloro-1,3,5-triazine XC as an efficient catalyst for the ring-opening of epoxides with thiols under solvent-free conditions (Table , entry 8) . Using 2 mol % of catalyst, the corresponding β-hydroxy sulfides were synthesized in excellent yields (95%-quant.)…”
Section: Nonenantioselective Organocatalytic C–s Bond Formationsmentioning
confidence: 99%
“…Bandgar and co-workers developed 2,4,6-trichloro-1,3,5-triazine XC as an efficient catalyst for the ring-opening of epoxides with thiols under solvent-free conditions (Table , entry 8) . Using 2 mol % of catalyst, the corresponding β-hydroxy sulfides were synthesized in excellent yields (95%-quant.)…”
Section: Nonenantioselective Organocatalytic C–s Bond Formationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] As for example, TCT and DMF (TCT-DMF adduct) have been used for chlorination of aliphatic alcohols, 8 but there have not been any elaborative studies about using such TCT-DMF adduct for chlorination of glycosyl substrates.…”
mentioning
confidence: 99%
“…Recent results from our laboratory had shown that simple and readily available cyanuric chloride can assist some important organic reactions (33,34). In continuation to our ongoing program, we would like to report a mild, practical, and efficient method for the opening of epoxides with substituted amines using catalytic amounts of cyanuric chloride under solvent-free conditions (Scheme 1).…”
mentioning
confidence: 99%